EFFECTIVE METHODS FOR INCREASING STUDENT MOTIVATION IN ENGLISH LANGUAGE TEACHING - Maxmudova Farzona (American Journals Publishing, 2026)
This article is devoted to studying effective methods of increasing student motivation in English language teaching. The article analyzes the concept of motivation, its significance in the educational process, as well as interactive and innovative methods applied in practical lessons. The research results are aimed at enhancing student participation, increasing interest in learning, and improving language acquisition efficiency.
Keywords: Motivation, English language, teaching methods, interactive methods, student engagement